Authentication and Key Agreement Protocol for Ad Hoc Networksbased on the Internet of Things paradigm : A Thesis Summary (Informatica, 2016)
The article summarizes the key findings of the doctoral thesis written by the author. The content of the thesis is based on the research fields of authentication and key agreement protocols (AKAP) for wireless sensor networks, and the internet of things (IOT). They key contribution of the thesis is a novel user AKAP for ad hoc networks, which is tailored for the IOT environment.